Murine Models Provide New Insights Into Pathogenesis of Chronic Graft-Versus-Host Disease in Humans - Song, Qingxiao; Kong, Xiaohui; Martin, Paul J.; Zeng, Defu (Frontiers in Immunology, 2021)
Allogeneic hematopoietic cell transplantation (allo-HCT) is a curative therapy for hematologic malignancies, but its success is complicated by graft-versus-host disease (GVHD). GVHD can be divided into acute and chronic types. Acute GVHD represents an acute alloimmune inflammatory response initiated by donor T cells that recognize recipient alloantigens. Chronic GVHD has a more complex pathophysiology involving donor-derived T cells that recognize recipient-specific antigens, donor-specific antigens, and antigens shared by the recipient and donor. Antibodies produced by donor B cells contribute to the pathogenesis of chronic GVHD but not acute GVHD. Acute GVHD can often be effectively controlled by treatment with corticosteroids or other immunosuppressant for a period of weeks, but successful control of chronic GVHD requires much longer treatment. Therefore, chronic GVHD remains the major cause of long-term morbidity and mortality after allo-HCT. Murine models of allo-HCT have made great contributions to our understanding pathogenesis of acute and chronic GVHD. In this review, we summarize new mechanistic findings from murine models of chronic GVHD, and we discuss the relevance of these insights to chronic GVHD pathogenesis in humans and their potential impact on clinical prevention and treatment.